Efficacy and safety of Botulinum toxinA for improving esthetics in facial complex: A systematic review - Ganjigatti, R.R.; Bennani, V.; Aarts, J.M.; Choi, J.J.E.; Brunton, Paul (2021)
Aim: To evaluate efficacy and safety of Botulinum toxinA for improving esthetics in the facial complex and correlating them to the dosage and side effects through a systematic review. Methods: A literature search was performed using PubMed, Medline, Web of Sciences, and Scopus databases. Quality of studies was appraised through the GRADE system. This review follows the ‘Preferred reporting items for systematic review and meta-analysis protocols’ (PRISMA-P) 2015 statement. Efficacy was analyzed through improvement rate and effect sizes. Graphical comparison of efficacy and ocular adverse effects (adverse effects around the eye) at various anatomical locations was made by calculating the average improvement rate and adverse events. Results: Twenty-five studies were included in this systematic review after application of the inclusion criteria. Moderate to severe cases in glabellar, lateral canthal, and forehead regions showed higher improvement rates between 20U to 50U, with an effect lasting up to 120 days. Gender and age seemed to have a direct effect on efficacy. Headaches were the most common adverse effect, followed by injection site bruising; all adverse effects resolved within 3-4 days. Conclusions: Treatment with Botulinum toxinA to enhance esthetics of facial complex is efficient and safe at all recommended dosages. Presence of complexing proteins influenced the efficacy of BoNT-A. undesirable muscular adverse effects around the eyes were more predominant when treating the glabellar region. There was no correlation found between the BoNT-A dosage and side effects, however, an increase in dosage did not always lead to an increase in efficacy.